The Kindergarten teachers’ perceptions of children’s theater and the reality of their use of it (A field study): Kindergarten teachers’ perceptions of children’s theater and the reality of their use of it (A field study) (Journal of Hama University, 2025)
The current research aimed to study kindergarten teachers’ perceptions of children’s theater in the city of Jableh and the obstacles to their use of it. And revealing the differences between the average scores of the sample members on the questionnaire of perceptions about children’s theater and the reality of its use in the city of Jableh according to the variables of the study (type of kindergarten, academic qualification, years of experience). The research adopted the descriptive survey method, and the research community included all kindergarten teachers in the city of Jableh, numbering (175) teachers, where (107) questionnaires were distributed to the teachers. The results showed that the most important perceptions about children’s theater is that children’s theater teaches children values, skills, and concepts. Children's theater achieves the comprehensive development of the child in various areas of development. Children's theater enhances logical intelligence by training them in abstract thinking. The most important obstacle that limits the reality of its use is the lack of experience that prevents teachers from implementing forms of theatrical presentation, and their lack of training prevents them from implementing theater activities. Child. There are also no statistically significant differences at the significance level (= 0.05a) between the average scores of the sample members on the questionnaire of perceptions about children’s theater and the reality of its use in the city of Jableh according to the variables of the study (type of kindergarten, educational qualification, years of experience).
Keywords: teachers’ perceptions, children’s theatre, kindergarten, kindergarten teachers.